STRATEGI KOMUNIKASI PUBLIC RELATIONS DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI JAWA TIMUR UNTUK MENINGKATKAN CITRA DI MATA PUBLIK - Mardiana, Wike; Hamim, Hamim; Widiyanto, Kendry (Universitas 17 Agustus 1945 Surabaya, 2018)
The purpose of this study is to provide an overview of communication strategy of PublicRelations that executed by DinasKomunikasidanInformatika of East Java Province in order toimprove positive image according to Two-Way Symetric theory and supporting theory by HaroldLasswell. The writer applies descriptive qualitative method in compiling this thesis. DinasKomunikasidanInforatika of East Java Province. The purpose of this study is to explain anyphenomenon in details by specific data collection. This study describing communication strategy ofPublic Relations that executed by DinasKomunikasidanInformatikaof East Java Provience. The resultof study shows that strategy executed by DinasKominfo to improve their image in front of public areby creating website, creating facebook account, and creating twitter account in order to ease public inmaking any complain and to ease public finding any information. Public Relations DinasKominfousing two approaching strategy including persuasive and educative approaching, and cooperationapproaching with internal public and external public.Keywords : Public Relations Strategic, Dinas Komunikasi dan Infromatika Provinsi Jawa Timur,Image.